Loss Aversion and Preferences in Interaction. (3rd March 2020) - Quinn, Philip; Cockburn, Andy
Abstract : Many interfaces attempt to assist users by offering suggestions, predicting actions, or correcting user input. Although these attempts may often be beneficial, they will occasionally fail, and prior research from psychology and behavioral economics on loss aversion suggests that such failures may have an overweighted impact on subjective preferences. To better understand the relationship between interface outcomes and subjective preferences, we adapted to interaction a model from behavioral economics describing reference-dependent preferences . Two experiments examined our model's predictions: both involved word-snapping interface assistance during text selection, with subjects choosing whether they preferred unassisted text selection (no snapping) or assisted text selection (snapping). In Experiment 1, the word-snapping feature could be disabled when it was unhelpful by backtracking the selection, which required progress losses in terms of target characters selected. In Experiment 2, word-snapping could be disabled by pressing a modifier key and waiting for an animation to complete, without need for the loss of target characters. Time and error performance with both experimental methods were comparable. The model predicts an aversion to progress losses in Experiment 1 that should be neutralized in Experiment 2, and the results of both experiments conformed to these predictions. We discuss the implications of the model as a platform for understanding user preferences more broadly, especially when considering interfaces that risk periodically failing to meet user expectations.